Ответы и объяснения

2013-06-24T09:27:13+04:00
Лучший Ответ!
  • AlbuRin
  • светило науки
2013-06-24T09:43:18+04:00

3^(2x+3)>=1/81

3^(2x+3)>=(1/3)^4

3^(2x+3)>=3^(-4)

2x+3>=-4

2x>=-4-3

2x>=-7x>=-3.5

 

Ответ.   [ -3.5;   +бесконечности)

 

 

 

 

3)   log_4(2x+8)=2

      log_4(2x+8)=log_4 4^2

      2x+8=16

      2x=16-8

      2x=8

      x=4

      ОДЗ  2x+8>0     2x>-8      x>-4

Ответ.     4

 

6)     V(2x-3)=V(x+1)

        Возведем  обе  части  в   квадрат

        2x-3= x+1

        2x-x=1+3

        x=4

Проверка.   V(2*4-3)=V5      V(4+1)=V5            V5=V5

Ответ.       4